AN EXPERIMENT ON THE PROPOSED ONLINE ASSESSMENT AND EXAMINATION METHOD AT DALAT UNIVERSITY - Thi Thu Phuong Ta; Bao Tuyen Huynh; Phuoc Huy Dang (Tạp chí Khoa học Đại học Đà Lạt)
Digital transformation is one of the key tasks of the education field. In this context, online teaching is becoming a potential solution in education to provide learners with a flexible learning environment that is independent of space and time. This trend has become even more urgent as the world has just experienced the global COVID-19 pandemic. Along with online teaching are methods of online assessments and examinations. The biggest challenges to online assessments and examinations are internet speed, authentication of the examinee’s identity, and test authenticity, especially for classes with large numbers of students. In this article, we propose an online oral exam process that can be applied to a large class but still ensures seriousness, fairness, and objectivity. Experiments conducted in 11 courses taught and assessed at Dalat University during the second semester of the 2020–2021 school year and the first semester of the 2021–2022 school year are discussed to illustrate the process.